Rare Causes of Unilateral Sensorineural Hearing Loss in Adults: Our Experience - Tyagi, Amit Kumar (Indian J Otolaryngol Head Neck Surg, 2020)
Bilateral hearing loss is attributed to almost 50% of times with genetic etiology, while most unilateral sensorineural hearing loss (USNHL) are not attributable to it. Limited literature is available on epidemiology of USNHL. Etiology of USNHL is very diverse and vast, it ranges from as common as Meniere’s disease to as rare as an electric shock injury. A prospective study was carried out to find rare causes of USNHL in adults. In this manuscript, we present a case series of 7 rare etiologies of USNHL in adults like auditory neuropathy, chemoradiotherapy, dialysis-induced SNHL, common cavity inner ear malformation, multiple sclerosis, acute otitis media-induced SNHL and vertebrobasilar dolichoectasia. This study discusses the rare possible etiologies of USNHL that can be easily missed if these are not ruled out properly. We present these cases to consider these heterogeneous and distinct causes of USNHL because of rarity of these etiologies. If such an etiology is diagnosed in time, they may be managed effectively.